Palynological characteristics of selected Lamioideae taxa and its taxonomic significance. Issue 3 (21st September 2020) - Gul, Saba; Ahmad, Mushtaq; Zafar, Muhammad; Bahadur, Saraj; Zaman, Wajid; Ayaz, Asma; Shuaib, Muhammad; Butt, Maryam Akram; Ullah, Fazal; Saqib, Saddam; Nizamani, Mir Muhammad; Urooj, Zara
Abstract: Lamioideae comprised the second‐largest subfamily in Lamiaceae. Although considerable progress has recently been made in the taxonomic study of Lamioideae, the subfamily remains one of the most poorly investigated subfamily in Lamiaceae. Therefore, the present study was designed with the aim to document the pollen micromorphology of some selected Lamioideae taxa and its taxonomic significance from Pakistan. Pollen micromorphological features were observed using scanning electron microscopy. The pollen grains are monad, tricolpate, radially/bilateral symmetrical. The pollen grains were small to medium‐sized having oblate, oblate/subspheroidal, and subspheroidal shape. Exine sculpturing was observed as reticulate, microreticulate, and bireticulate. The colpus surface ornamentation was found as verrucate, gemmate, scabrate, and psilate. There was a considerable variation between the species in the micromorphology, that is, the coarseness of the reticulum, thickness of the muri comprising the reticulum and the number of secondary lumina per primary lumen. Hence, this study documented the pollen morphology of some selected taxa of the subfamily Lamioideae from Pakistan and strengthens the taxonomic identification of subfamily based on pollen characters, which helps in the correct identification, discrimination of the species of Lamioideae at generic and species level. Abstract : Pollen micromorphology of selected Lamioideae taxa was carried out through scanning electron microscopy and their taxonomic significance. A significant variation was observed in exine sculpturing that helps in the identification and discrimination of the species at generic and species level. Pollen traits of Pakistani Lamioideae taxa were found significant to strengthen the taxonomy of the subfamily.